Asylum
The story of Baaba Andoh, a young Ghanian woman who goes in search of her father for his blessing on her impending marriage to the young man she loves. Her joy at finding him turns into a nightmare as the parent insists she submit to his choice of marriage to an old man, and that she undergo female circumcision as is the custom in his tribe. She is forced to flee her father's village, seeking refugee status in the U.S. Instead she becomes enmeshed in the U.S. immigration system.